Jeziki visokega šolstva 2012-2023 - Kalin Golob, Monika (Jezik in slovstvo, 2023)
We identify (good) practices for language regulation in Slovenian higher education through a review of the legal and formal provisions and activities for the development and preservation of the Slovenian language, a definition of the concept of language care in higher education, and interviews with those responsible. Over the last ten years, many activities and experiences have emerged that allow for the effective exchange and integration of foreign students and professors, but such activities are often left to the initiative of teaching and administrative staff, their ingenuity and motivation. Recommendations are made based on the need to overcome the polarity between Slovene and foreign languages in Slovenian higher education and science. First and foremost, the state and universities should regard financial resources dedicated to internationalisation as support for the Slovene language, including: language courses; information technology for translators, digitisation of Slovene and the development of terminology in higher education; and, above all, the effective organisation of all recommended activities.
Keywords: care for the Slovene language; digitalizacija; digitisation; higher education; internacionalizacija; internationalisation; jezikovna politika; jezikovne pisarne; language offices; language policy; skrb za slovenski jezik; Slovene; slovenščina; visoko šolstvo